[Breaking the habit ; Mixed marriage ; Inno Sotto [videorecording] - Lazaro, Cheche (The Probe Team, 1992)
Sr. Christine Tan, Sr. Mary John Mananzan and Sr. Cris. Lucero in their evangelistic efforts armed at seeing God through the poor, imprisoned and the neglected. Looks at intermarriages and Filipino mail-order brides. Top fashion designer, Inno Sotto in his fashion displays and commercial ads modeling.